Clinical Practice Guidelines for Pancreatic Cancer 2019 From the Japan Pancreas Society: A Synopsis - Okusaka, Takuji; Nakamura, Masafumi; Yoshida, Masahiro; Kitano, Masayuki; Uesaka, Katsuhiko; Ito, Yoshinori; Furuse, Junji; Hanada, Keiji; Okazaki, Kazuichi (Pancreas, 2020)
Clinical Practice Guidelines for Pancreatic Cancer were first published in 2006 by the Japan Pancreas Society, and they were revised in 2009, 2013, and 2016. In July 2019, the Clinical Practice Guidelines for Pancreatic Cancer 2019 were newly revised in Japanese. For this version, we developed the new guidelines according to the Minds Manual for Guideline Development 2017, which includes the concepts of GRADE (Grading Recommendations Assessment, Development, and Evaluation), to enable a better understanding of the current guidelines. The guidelines show algorithms for the diagnosis, treatment, and chemotherapy of pancreatic cancer and address 7 subjects: diagnosis, surgical therapy, adjuvant therapy, radiation therapy, chemotherapy, stent therapy, and supportive and palliative medicine. They include 56 clinical questions and 84 statements. There are statements corresponding to clinical questions, evidence levels, recommendation strengths, and agreement rates. These guidelines represent the most standard clinical and practical management guidelines at this time in Japan. This is the English synopsis of the Clinical Practice Guidelines for Pancreatic Cancer 2019 in Japanese and is an attempt to disseminate the Japanese guidelines worldwide for introducing the Japanese approach for clinical management of pancreatic cancer.